2015
DOI: 10.1111/jorc.12132
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Factors on Quality of Life of Patients With Chronic Kidney Disease in Greece

Abstract: In general terms, people with CKD patients present with a poor QoL. Apart from the burden of the renal disease per se, social and economic factors (divorce, financial difficulties) seem to aggravate their status, especially in this period of financial crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
(81 reference statements)
2
18
0
3
Order By: Relevance
“…The low levels of depression in spouses in the present study are in accordance with the low levels of depression in CKD patients of the same Nephrology Department (University Hospital of Ioannina), found in the study of Ikonomou et al [52]. This agrees with the remark of Khaira et al [28] that CKD patients who are dialysis dependent and their spouses interact in terms of depression levels.…”
Section: Discussionsupporting
confidence: 93%
“…The low levels of depression in spouses in the present study are in accordance with the low levels of depression in CKD patients of the same Nephrology Department (University Hospital of Ioannina), found in the study of Ikonomou et al [52]. This agrees with the remark of Khaira et al [28] that CKD patients who are dialysis dependent and their spouses interact in terms of depression levels.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies reflected these findings. [23][24][25] In our study lower QOL scores for work among Omani adults can be attributed to the lower rate of labor force participation, and poor family support. Employed adults with a lower annual income are strongly associated with a lower QOL score.…”
Section: Discussionmentioning
confidence: 48%
“…Our center has embraced the philosophy that every human has the right to access health care free with dignity, irrespective of cast, creed, color, and religion. [7][8][9]11,[13][14][15][16] This institution has worked to provide lifelong state-of-the-art renal care facilities to all patients, free of cost. In a country where the health care budget is only 0.8% of the GDP, SIUT, with the help of philanthropists, has made it possible to provide all of these facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Our dialysis program is integrated with transplant procedures and a life-long follow-up with free medications. [7][8][9]11,[13][14][15][16] Although every treatment at SIUT is provided free of cost, still there are access and other socioeconomic problems, which result in less than perfect compliance to treatment protocols. [17][18][19] An informal survey by our department found that a significant number of patients do not turn up again for regular dialysis and many also miss more than one session of dialysis.…”
Section: Introductionmentioning
confidence: 99%